2018
DOI: 10.1007/s00787-018-1159-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions in psychosis in children and adolescents: a systematic review

Abstract: There is some evidence supporting the effectiveness of psychological interventions in EOP. However, most research on adolescents is focused on CRT and its effects on cognitive deficits. More studies on the effects of psychological interventions in EOP are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…DEP and PSY were similalry negatively associated to family flexibility, satisfaction and communication. This result also corresponds with literature suggesting that DEP and PSY may either be exacerbated by adverse external experiences, such as those related to family functioning; or negatively impact the level of the family relationships of the carrier [25,75]. In contrast, ANX positively tied to family flexibility, satisfaction, communication and the overall family functioning (as reflected by the family ratio).…”
Section: Psychopathological Dimensions and Family Functioningsupporting
confidence: 88%
“…DEP and PSY were similalry negatively associated to family flexibility, satisfaction and communication. This result also corresponds with literature suggesting that DEP and PSY may either be exacerbated by adverse external experiences, such as those related to family functioning; or negatively impact the level of the family relationships of the carrier [25,75]. In contrast, ANX positively tied to family flexibility, satisfaction, communication and the overall family functioning (as reflected by the family ratio).…”
Section: Psychopathological Dimensions and Family Functioningsupporting
confidence: 88%
“…Psychotherapy is generally considered the most appropriate initial treatment of childhood depression [102], although a Cochrane review concluded that the relative benefits of pharmacotherapy, psychotherapy, or the combination thereof have not been clearly demonstrated empirically [103]. Psychological interventions for psychosis in adolescence appear to be helpful for cognition and functioning, if not psychosis itself [104]. However, there is very little empirical information about psychotherapy in juvenile psychotic depression.…”
Section: Treatmentmentioning
confidence: 99%
“…Indeed, they are the main centres of MSS expertise. Also, there is some evidence supporting the effectiveness of psychological interventions in Early Onset Psychosis [33]. Very few children received cognitive remediation or workshops of social abilities.…”
Section: Treatmentmentioning
confidence: 99%